Inhibited neural response during interpersonal conflict: insights from fNIRS hyperscanning - Cao, Kang; Zhang, Mingming; Zhang, Yuxuan; Li, Jie (Frontiers in Psychology, 2025)
Interpersonal conflict is a core yet complicated part of social interaction, involving complex mental and emotional processes. However, the neural mechanisms underlying interpersonal conflict are still not fully understood. This study employed functional near-infrared spectroscopy (fNIRS) hyperscanning to explore the brain activity related to interpersonal conflict through both passive video viewing and active role-playing paradigms. The results revealed an unexpected activation pattern – brain activity was highest at rest, lower during conflict, and lowest during neutral interactions (i.e., rest > conflict > neutral) in all ROIs except the rTPJ during active role-playing. This indicates a cortical deactivation effect when people engage in social processing. Additionally, the study found that inter-brain synchronization (IBS) between the two participants' brains decreased significantly during conflict compared to non-conflict conditions. These findings provide neurocognitive evidence for disrupted interpersonal alignment during conflict and highlight potential intervention targets—such as perspective-taking and interpersonal attunement—for enhancing social functioning in challenging interactions.